Assistive Technology and Older Adults in Disasters: Implications for Emergency Management - Akyuz, Halil Ibrahim; Avan, Cagri (Nobel Tip Kitabevleri, 2024)
Individuals with special needs need diff erent things to sustain their daily lives. It is important for these individuals to use assistive technologies according to their needs. Especially in disaster situations, it is a necessity for these individuals to be prepared to respond to their needs and to sustain their lives. Planned studies should be carried out for individuals with special needs before, during and aft er the disaster and a structure should be created to meet the urgent needs of the individual. In the disaster process, some measures should also be taken for assistive technologies according to the condition of the individual. Assistive technologies required for individuals with visual impairment, on the other hand, cause diffi culties for individuals in disaster processes, especially since physical devices are needed. Th erefore, there is a need to take state-supported measures for their procurement. Beyond physical disabilities, assistive technologies for mental disabilities are not suffi - ciently developed and studies that support the learning process come to the fore. While the primary assistive technologies for individuals with communication diffi culties are tools that will concentrate attention, they are eff ective in raising awareness of the individual before the disaster and teaching the rules. As a result, although there are many tools to facilitate the daily lives of individuals with special needs, their eff ective use in disaster periods will be benefi cial for individuals and their families.